Investigation of the Impact of Inhalation Aromatherapy on Relaxation and Wellbeing in a Young Adult Population - Sasse, Astrid; Sheridan, Helen; Sagheri, Darius (My University, 2024)
Background and Purpose: Aromatherapy is the systematic use of essential oils extracted from plants to support health and wellbeing. Recent clinical studies have shown that aromatherapy has potential benefits as a non-pharmacological approach to alleviate stress and anxiety. The aim of this project was to evaluate the impact of inhalation aromatherapy on relaxation and wellbeing in a young adult population. Methods: Two double-blind randomised controlled pilot studies were conducted in 2021 and 2022, one using room diffusion (Study 1) and one study using an aromastick (Study 2) to measure the effect on wellbeing, stress and anxiety in a young healthy adult population. Test and control formulations with essential oils were assessed for one week and four weeks, respectively. Both studies employed validated measurement tools (DASS-42, WEMWBS). Results: The results for Study 1 showed that participants in the test group reported reduced levels for stress and depression compared to the control group in 87.5% of participants (p = 0.0291 and p = 0.04, respectively). A trend was seen for anxiety, which was not significant (p = 0.25). In the second study, analysis of the wellbeing scores indicated a significant improvement for the test group in a paired t-test (p = 0.002). Conclusion: In these small pilot studies (n = 17 and n = 33), statistically significant effects were observed in favour of the test interventions. The robust design of the studies and the use of validated quantitative measurement tools were a good foundation on which to build future research.
PUBLISHED
Keywords: Inhalation aromatherapy, Stress and anxiety, Relaxation and wellbeing, Essential oil, Complementary therapy; Next Generation Medical Devices; Biomedical sciences; PHARMACEUTICAL CARE; PHARMACY PRACTICE; Pharmacognosy; Pharmacy